Field Efficacy of Some New Generation Insecticides Against Maize Aphid (Rhopalosiphum maidis) and its Effect on Yield (Journal of the Bangladesh Agricultural University, 2024)
A field experiment was conducted at the Field Laboratory, Department of Entomology, Bangladesh Agricultural University (BAU), Mymensigh during Rabi season of 2017-18 to find out the efficacy of some new generation insecticides against maize aphid and its effects on yield. BARI Hybrid Butta-9 variety was used as experimental crop and four insecticides viz. Imidagold 20SL@ 0.1, 0.3 & 0.5 ml/L; Ambush 1.8 EC@ 1.5, 2.5 & 3.0 ml/L; Hadhak 45WP@ 0.2, 0.4 & 0.6 g/L and Suspend 5SG@ 0.5, 1.0 & 1.5 g/L were used as experimental treatments. Results clearly showed Imidagold 20SL resulted in the greatest reduction of aphid infestation and increased the grain yield compared to the all tested insecticides where the doses of 0.5 ml/L and 0.3 ml/L of this insecticide were statistically similar. Thereafter, the result was followed by Ambush 1.8 EC, Hadhak 45WP and Suspend 5SG, respectively, while the highest plant infestation, the lowest grain yield and the lowest benefit cost ratio were obtained from untreated control. Moreover, there had a positive and significant co-relation between percent reduction of plant infestation and yield increase. In addition, data also revealed that the use of Ambush 1.8 EC @ 3.0 ml/L performed second best treatment. Therefore, it can be concluded that the maize farmers can use Imidagold 20SL@ 0.3 ml/L or Ambush 1.8EC @0.3 ml/L for effective management of maize aphid under field condition.J Bangladesh Agril Univ 18(3): 565–570, 2020https://doi.org/10.5455/JBAU.14970